2016
DOI: 10.1080/10410236.2015.1089467
|View full text |Cite
|
Sign up to set email alerts
|

Cyberframing Cancer: An Exploratory Investigation of Valenced Cybercoping on Cancer Blogs

Abstract: Although scholarship on coping with cancer implies many ways that coping is communicative, the discursive features of coping have been understudied. The purpose of the present investigation was to theorize the content of cancer blogs, a form of cybercoping, by examining valenced coping-relevant frames that bloggers use to describe their experiences with cancer. This research is both theoretically and methodologically innovative. Theoretically, we advance the concept of cyberframing by connecting the rather dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Vos and Buckner 4 analyzed 25,598 tweets about H7N9 (also known as bird flu) virus: they concluded that most of the tweets contained sensemaking information rather than efficacy information that would be useful for responding to the crisis appropriately. Donovan et al 7 conducted a content analysis of 194 cancer blog entries. They found that more than 90 percent of cancer blog posts were written based on a valenced frame: either negative, positive, or balanced.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Vos and Buckner 4 analyzed 25,598 tweets about H7N9 (also known as bird flu) virus: they concluded that most of the tweets contained sensemaking information rather than efficacy information that would be useful for responding to the crisis appropriately. Donovan et al 7 conducted a content analysis of 194 cancer blog entries. They found that more than 90 percent of cancer blog posts were written based on a valenced frame: either negative, positive, or balanced.…”
Section: Related Workmentioning
confidence: 99%
“…Posts with various health-related topics including infectious disease, 3,4 alcohol, 5 obesity, 6 and cancer have been uploaded by SNSs users. 7 Previous studies have focused on the amount, 8 subtopics, 9,10 and content of the SNS posts that were uploaded by individual users. 11 Also, analyzing the use of SNSs operated by public health authorities has taken another part of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…(2010) conduct a content analysis of the tweets in the healthcare domain on medicines or antibiotics and their effects, reactions, and uses. Other studies are conducted on alcohol consumption (Moreno et al., 2012), cancer blog posts (Donovan et al., 2017), diabetes data (Shaw and Karami 2017), and consumption of e‐cigarettes (Lazard et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Scanfeld et al (2010) conduct a content analysis of the tweets in the healthcare domain on medicines or antibiotics and their effects, reactions, and uses. Other studies are conducted on alcohol consumption (Moreno et al, 2012), cancer blog posts (Donovan et al, 2017), diabetes data (Shaw and Karami 2017), and consumption of e-cigarettes (Lazard et al, 2017). Yoo et al (2020) conducted a study on the dimensions of social media platforms and humanitarian crisis from the supply side, that is, to understand the phenomenon of building follower networks by HOs on social media platforms.…”
Section: Production and Operations Managementmentioning
confidence: 99%
“…financial barriers, fertility, posttreatment symptoms, posttraumatic stress and anxiety symptoms). In addition, from a recent content analysis of 194 cancer blog posts, most were framed with a positive or balanced with low affect valence (Donovan et al, 2017). And specifically among young adult cancer patients, 10 main themes were identified (e.g.…”
Section: Introductionmentioning
confidence: 99%